Exploring the Role of P2X Receptors in Alzheimer’s Disease - Godoy, Pamela Andrea; Ramírez-Molina, Oscar; Fuentealba, Jorge (Frontiers in Pharmacology, 2019)
Several studies have pointed to soluble oligomers of beta amyloid peptide (SOAβ) as the principal neurotoxic agents responsible for the generation of synaptotoxic events that can explain the main symptoms of Alzheimer’s disease (AD). Among the toxic features associated with SOAβ, one of the most notorious is the formation of a non-selective pore-like structure in the plasma membrane, which may partly explain the overload of intracellular Ca2+. There is evidence that the pore causes leakage of key intracellular compounds, such as ATP, to the extracellular milieu. Extracellular ATP can act as a ligand for P2X receptors (P2XR), which are ligand-gated ion channels (LGICs) widely expressed in both neuron and glial cells and act as neuromodulators of synaptic activity by promoting Ca2+ entry which facilitates neurotransmitter release. There is abundant evidence correlating the overexpression of these receptors to neurodegenerative diseases, including AD, thus opening the possibility that P2XR could potentiate the toxic mechanisms induced by SOAβ and contribute to intracellular Ca2+ overload in neurons and other mechanisms related to glial activation and inflammation. In this review, we correlate scientific evidence related to the main toxic effects induced by SOAβ and those that are mediated by purinergic P2XR. The data suggest that these purinergic receptors participate in the deleterious cellular and molecular effects of SOAβ that lead to the pathogenesis of AD. This information sheds light on the participation of new components in SOAβ toxicity that could be interesting as pharmacological targets for the development of molecular or chemical compounds able to modulate them.